(3eHGOF GdeMGSHI GdeGdjI (B:s (3GdGUhd GdYdejI aj JMVjQ GdbhGFe GdeMGSHjI (B/s - (3GdUaGQ, gGOj QVGs ((3YeGf(B: s (3OGQ GdefGgL(B, s, 2003)
(3GdeMJhjGJ (B: (3JegjO(B-(3ebOeI(B-(3GdLRA GdChd (B: (3ehGRjf GdeQGLYI hGdbhGFe GdeGdjI GdeMGSHjI (B: (3GdaUd GdChd (B: (3JMVjQ GdMSGHGJ GdNJGejI (B: (3eaghe ejRGf GdeQGLYI (B: (3GdaUd GdKGfj (B: (3YQV GdbhGFe GdeMGSHjI (B: (3CgejI YQV GdbhGFe GdeMGSHjI (B: (3GdaUd GdKGdK (B: (3GdeHGOF GdeMGSHjI hGdbhGFe GdeMGSHjI (B: (3GdaQhV GdeMGSHjI(B-(3GdLRA GdKGfj (B: (3GdJShjGJ GdLQOjI ddMSGHGJ GdhgejI (B: (3GdaUd GdQGHY (B: (3GdJShjGJ heHOC GdebGHdI (B: (3eHOC ebGHdI GdeUQhaGJ HGdEjQGOGJ (B: (3GdaUd GdNGeS (B: (3GdJShjGJ GdLQOjI ddeUQhaGJ (B: (3YdGbI GdeUQha HGdaJQI (B: (3GdaUd GdSGOS (B: (3GdJShjGJ GdLQOjI ddEjQGOGJ (B: (3GdEjQGOGJ ef ZjQ GdfTGW GdJLGQj(B-(3GdLRA GdKGdK (B: (3GdeMGSHI Yf GdCUhd GdeJOGhdI (B: (3GdaUd GdSGHY (B: (3GdeMGSHI Yf GdfbOjI aj GdUfOhb (B: (3CeGfI GdUfOhb hMSGH GdUfOhb (B: (3GdaUd GdKGef (B: (3GdeMGSHI Yf GdfbOjI aj GdHfc (B: (3GdeYGedGJ GdeUQajI (B: (3GdaUd GdJGSY (B: (3GdeMGSHI Yf GdeOjfhf (B: (3YedjGJ GdHjY GdBLd (B: (3GdaUd GdYGTQ (B: (3GdeMGSHI Yf ChQGb GdbHV (B: (3EKHGJ ChQGb GdbHV (B: (3GdaUd GdMGOj YTQ (B: (3GdeMGSHI ddGSJKeGQGJ aj GdChQGb GdeGdjI (B: (3eaghe GdGSJKeGQGJ bUjQI GdCLd (B: (3GdaUd GdKGfj YTQ (B: (3MSGHGJ GdeNRhf GdSdYj (B: (3WQb GdbjO ddMSGHGJ GdeNRfjI(B-(3GdLRA GdQGHY (B:(3GdCUhd GdKGHJI (B: (3GdaUd GdKGdK YTQ (B: (3GdCUhd GdKGHJI GdedehSI (B: (3cdaI GdCUhd GdKGHJI (B: (3GdaUd GdQGHY YTQ (B: (3GdGSJZfGA Yf GdCUhd GdKGHJI (B: (3MGdGJ GdGSJZfGA Yf GdCUhd (B: (3GdaUd GdNGeS YTQ (B: (3GdCUhd GdeJfGbVI, GdehGQO GdWHjYjI (B: (3NUGFU GdCUhd GdeJfGbVI (B: (3GdaUd GdSGOS YTQ (B: (3GdCUhd GdKGHJI ZjQ GdedehSI (B: (3NUGFU GdCUhd ZjQ GdedehSI(B-(3GdLRA GdNGeS (B: (3GdeMGSHI Yf GdeWdhHGJ hMbhb GdedcjI (B: (3GdaUd GdSGHY YTQ (B: (3GdeWdhHGJ (B: (3GdeWdhHGJ bUjQI GdCLd (B: (3GdaUd GdKGef YTQ (B: (3Mbhb GdedcjI (B: (3Mbhb GdedcjI ddeTQhYGJ GdaQOjI(B.s
(3HjHdjhZQGajG U(B.431s
Keywords: (3GYOGO GdbhGFe s; (3GdJbGQjQ GdeGdjIs; (3eMGSHI eGdjIs